Eight Questions about Brain Drain - Gibson, John (The World Bank, 2011)
High-skilled emigration is an emotive issue that in popular discourse is often referred to as brain drain, conjuring images of extremely negative impacts on developing countries. Recent discussions of brain gain, diaspora effects, and other advantages of migration have been used to argue against this, but much of the discussion has been absent of evidence. This paper builds upon a new wave of empirical research to answer eight key questions underlying much of the brain drain debate: 1) What is brain drain? 2) Why should economists care about it? 3) Is brain drain increasing? 4) Is there a positive relationship between skilled and unskilled migration? 5) What makes brain drain more likely? 6) Does brain gain exist? 7) Do high-skilled workers remit, invest, and share knowledge back home? And 8) What do we know about the fiscal and production externalities of brain drain?